Redesign of coconut grater blades to minimize coconut milk reduction using the reverse engineering method - Lorenza, Hilma Efrina (Jurnal Inovasi Pangan dan Gizi, 2025)
Background: Indonesia is one of the countries with the highest coconut production and productivity levels in the world. The use of coconut in Indonesia is often employed in the production of coconut milk, both in households, small industries, and large industries. To produce coconut milk, grated coconut is required. Grated coconut is obtained from coconuts that have been grated using a grating machine. This study used a coconut grating machine available at Telkom University, which produces grated coconut with a significant reduction in coconut milk yield, namely 56.25% of the previous grated coconut weight. The study aims to reduce the reduction in coconut milk yield to achieve a more optimal result by using the Reverse Engineering method with the assistance of a 3D Scanner. Methods: This study employed a reverse engineering approach comprising systematic stages of field observation, data acquisition, 3D scanning, and component redesign to develop an optimized coconut grater. The redesigned model was then tested and compared with the existing grater to evaluate improvements in grating performance and coconut milk extraction efficiency. Findings: The 3D Scanner results were then processed using Solid Edge software, which functions to display the 3D design that can be analyzed and modified according to the research objectives. Once the necessary modifications were identified, the next step was the redesign process. The redesign process was carried out using Autodesk Fusion to redesign the new or proposed grater. A reduction of 28.33% was obtained, with a difference of 27.92% from the previous grater reduction. With a reduction of 27.92%, coconut milk production became more optimal compared to the previous results. Conclusion: This study concluded that redesigning the coconut greater using the Reverse Engineering method effectively reduced the coconut milk reduction rate from 56.25% to 28.33%, resulting in a 27.92% improvement in extraction efficiency. Novelty/Originality of this article: This study introduces an improved coconut greater design developed through the Reverse Engineering method using 3D scanning and CAD software, resulting in optimized grater tooth dimensions that significantly reduce coconut milk yield loss and enhance extraction efficiency.